Infrastructures of digital humanities. Issue 1 (22nd October 2020) - Sula, Chris Alen; Craig, Kalani; Dalmau, Michelle; Humphreys, Alex; Hyvönen, Eero; Keah, Humphrey; Kiplang'at, Joseph; Lindquist, Thea; Weber, Nic
Abstract: This panel will convene participants from a range of roles and institutions to build on previous work in infrastructures of digital humanities: the organizational and structural aspects of the field responsible for collaboration, partnership, training and support, access, preservation, sustainability, and more. Information professionals play a key role in these infrastructures, from technical expertise to project management to training and support for methods and tools. Panelists from faculty, centers and institutes, and academic and digital libraries will address issues of capacity building, disciplinarity, and labor across various settings.